Implementation of electrochemical, optical and denuder-based sensors and sampling techniques on UAV for volcanic gas measurements: examples from Masaya, Turrialba and Stromboli volcanoes - Rüdiger, Julian; Bobrowski, Nicole (Atmospheric measurement techniques, 2018)
Abstract. Volcanoes are a natural source of several reactive gases (e.g., sulfur and halogen containing species) and nonreactive gases (e.g., carbon dioxide) to the atmosphere. The relative abundance of carbon and sulfur in volcanic gas as well as the total sulfur dioxide emission rate from a volcanic vent are established parameters in current volcano-monitoring strategies, and they oftentimes allow insights into subsurface processes. However, chemical reactions involving halogens are thought to have local to regional impact on the atmospheric chemistry around passively degassing volcanoes. In this study we demonstrate the successful deployment of a multirotor UAV (quadcopter) system with custom-made lightweight payloads for the compositional analysis and gas flux estimation of volcanic plumes. The various applications and their potential are presented and discussed in example studies at three volcanoes encompassing flight heights of 450 to 3300 m and various states of volcanic activity. Field applications were performed at Stromboli volcano (Italy), Turrialba volcano (Costa Rica) and Masaya volcano (Nicaragua). Two in situ gas-measuring systems adapted for autonomous airborne measurements, based on electrochemical and optical detection principles, as well as an airborne sampling unit, are introduced. We show volcanic gas composition results including abundances of CO2, SO2 and halogen species. The new instrumental setups were compared with established instruments during ground-based measurements at Masaya volcano, which resulted in CO2 ∕ SO2 ratios of 3.6 ± 0.4. For total SO2 flux estimations a small differential optical absorption spectroscopy (DOAS) system measured SO2 column amounts on transversal flights below the plume at Turrialba volcano, giving 1776 ± 1108 T d−1 and 1616 ± 1007 T d−1 of SO2 during two traverses. At Stromboli volcano, elevated CO2 ∕ SO2 ratios were observed at spatial and temporal proximity to explosions by airborne in situ measurements. Reactive bromine to sulfur ratios of 0.19 × 10−4 to 9.8 × 10−4 were measured in situ in the plume of Stromboli volcano, downwind of the vent.